Penerapan Karnaugh Map dengan Dasar Aljabar Boolean untuk Mendiagnosa Penyakit - Qirana Azmil Zamhur; Gani Gunawan; Respitawulan (Bandung Conference Series: Mathematics, 2023)
Abstract. One application of an expert system using the Karnaugh Map or commonly referred to as the K-Map is to make a conclusion on the results of diagnosing the symptoms of a disease. How can this system be used to draw conclusions from the diagnostic results? This article was written to introduce a way of making a conclusion from the arrangement of several symptoms of a disease. The way to do this is to create a user interface for the symptoms of the disease using a K-Map based on a predetermined diagnosis. Simplify K-Map to shorten the diagnostic process or generate conclusions in the process of creating a user interface. The case examples used in this article are several diseases that have similarities in the results of the diagnosis of symptoms. Based on the results of the work, it was found that K-Maps for three types of diseases along with their logic gates and K-Maps can speed up the process of generating conclusions in the form of diagnoses using Microsoft Access. Abstrak. Salah satu penerapan sistem pakar dengan menggunakan Karnaugh Map atau yang biasa disebut dengan K-Map adalah untuk membuat suatu kesimpulan hasil dari diagnosa gejala suatu penyakit. Bagaimanakah sistem tersebut dapat dilakukan untuk mendapat kesimpulan hasil diagnosa. Artikel ini ditulis untuk memperkenalkan suatu cara dalam membuat suatu kesimpulan dari susunan beberapa gejala suatu penyakit. Cara yang dilakukan adalah dengan membuat user interface gejala penyakit tersebut menggunakan K-Map berdasar pada diagnosa yang telah ditentukan sebelumnya. Penyederhanaan K-Map dilakukan untuk mempersingkat proses diagnosa atau menghasilkan kesimpulan dalam proses membuat user interface. Adapun contoh kasus yang digunakan dalam artikel ini adalah beberapa penyakit yang mempunyai kemiripan dalam hasil diagnosa gejalanya. Berdasarkan hasil pengerjaan didapatkan K-Map untuk tiga macam penyakit beserta gerbang logikanya serta K-Map juga dapat mempercepat proses dalam menghasilkan kesimpulan berupa diagnosa menggunakan Microsoft Access.